Meiotic Spindle Formation Following Inhibition of First Polar Body Formation in the Zhikong Scallop (Chlamys farreri Jones et Preston) - Li, Yongren; Zhang, Baolu; Liang, Shuang; Guo, Yongjun (Frontiers in Marine Science, 2021)
Fertilized Zhikong scallop (Chlamys farreri) eggs were treated with cytochalasin B (CB 0.5 mg/L) at 14–15 min postfertilization to inhibit first polar body formation. The eggs were then stained with fluorescein isothiocyanate-anti-α-tubulin and propidium iodide to examine their microtubule patterns and chromosome, respectively. Fluorescent microscope observations of treated eggs sampled every 2–3 min during meiotic maturation revealed meiotic apparatus assembly and correlated chromosome segregation. In CB-treated groups, meiosis I proceeded normally and produced two groups of dyads, with 19 in each group. Both dyad groups were retained in the eggs as they entered meiosis II. Two, three, or four asters (centrosome with microtubules around it) in meiosis II rearranged the spindle in several patterns: bipolar (24.0 ± 4.1 μm [long axis] × 18.3 ± 4.1 μm [diameter: metaphase plate]), tripolar (18.6 ± 3.9 μm × 9.9 ± 1.3 μm), separated bipolar (18.3 ± 2.8 μm × 11.2 ± 1.8 μm), and other unclassified spindle patterns. Corresponding chromosome segregation, including bipolar (18.9%), tripolar (38.9%), double bipolar (16.5%), and unclassified (25.6%), was observed during meiosis II in CB-treated eggs. The data indicated that chromosome segregation patterns determined by spindle patterns were critically influenced by the number of centrosomes in meiosis II eggs following inhibition of polar body 1 formation with CB.